2007
DOI: 10.1111/j.1467-9280.2007.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

When God Sanctions Killing

Abstract: ABSTRACT-Violent people often claim that God sanctions their actions. In two studies, participants read a violent passage said to come from either the Bible or an ancient scroll. For half the participants, the passage said that God sanctioned the violence. Next, participants competed with an ostensible partner on a task in which the winner could blast the loser with loud noise through headphones (the aggression measure). Study 1 involved Brigham Young University students; 99% believed in God and in the Bible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(51 citation statements)
references
References 6 publications
2
47
1
1
Order By: Relevance
“…In particular, participants did not think that exposure to violent literature increased aggression. Although some studies have shown that reading violent literature can increase aggression (Stockdale, Coyne, Nelson, & Padilla-Walker, 2013), including violent stories from the Bible (Bushman, Ridge, Das, Key, & Busath, 2007), much more research is needed on this topic before firm conclusions can be drawn. Although pediatricians and media researchers thought violent sports increased aggression in children, parents did not.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, participants did not think that exposure to violent literature increased aggression. Although some studies have shown that reading violent literature can increase aggression (Stockdale, Coyne, Nelson, & Padilla-Walker, 2013), including violent stories from the Bible (Bushman, Ridge, Das, Key, & Busath, 2007), much more research is needed on this topic before firm conclusions can be drawn. Although pediatricians and media researchers thought violent sports increased aggression in children, parents did not.…”
Section: Discussionmentioning
confidence: 99%
“…Activating or priming a religious frame in order to enhance prosociality is as likely to potentiate particularism as it is to activate any general humanitarianism. As seen in studies such as Bushman et al (2007) or Saroglou et al (2009), religiosity may have an activating effect on submissive or conformist attitudes. One implication of this also seen in other areas of the literature is that relying on compliance or conformity with sanctified extemal norms in order to promote prosocial behavior is often antithetical to the development of more sophisticated moral reasoning.…”
Section: Nonprosocial Effects: the Negative Influence Of Religious Prmentioning
confidence: 91%
“…However, the priming literature shows that this is, at best, a double-edged sword because both positive and negative goals can be sanctified. As Bushman et al (2007) demonstrated, activation of sanctification can have a negative effect when the prevailing religious norm is not prosocial or the target group violates religious values, or is merely a religious outgroup. In a different example, Burris and Jackson (1999) found that the more religious a participant was, the more the participant sympathized with a target victim in a depiction of partner abuse, but only when the victim affirmed his or her religious values.…”
Section: Nonprosocial Effects: the Negative Influence Of Religious Prmentioning
confidence: 99%
“…Bushman and Gibson (2011), for example, describe the CRTT as "a weapon that could be used [by the participants] to blast their pariner" (p. 30). Bushman et al (2007) found suppori for "theories proposed by scholars of religious terrorism who hypothesize that exposure to violent scriptures may induce extremists to engage in aggressive actions" (p. 204) in their study on university students' noise blasts after reading a passage from the Bible in which God sanctions violence. They conclude that "to the extent that religious extremists engage in prolonged, selective reading of the scriptures, focusing on violent retribution toward unbelievers instead of the overall message of acceptance and understanding, one might expect to see increased brutality" (p. 205).…”
Section: Clinical Relevancementioning
confidence: 98%